Relationship between Triage Response Time and Patient Satisfaction in the Emergency Room of Prof. Dr. Margono Soekarjo Purwokerto Hospital - Arifianti, Dani; Etlidawati (UM Purwokerto Press, 2025)
Emergency services are immediate, fast, accurate, and precise to prevent death or disability. Response time is required for a patient to receive appropriate assistance based on the severity of their condition from the moment they enter the Emergency Department (ED), with a standard of 5 minutes.This quantitative correlational study used a cross-sectional approach, purposive sampling, and a chi-square test for analysis. The study involved 97 respondents, with the fastest response time in the ED being two minutes (65 respondents) and the longest being six minutes. The patient satisfaction questionnaire results indicated that 40 respondents (41.2%) were very satisfied. Cross-tabulation showed that the highest percentage of very satisfied respondents (51.3%) were those who experienced a quick response time.There was a correlation between triage response time and patient satisfaction, p = 0.002 The study involved 97 respondents, with the fastest response time in the ED being two minutes (65 respondents) and the longest being six minutes. The patient satisfaction questionnaire results indicated that 40 respondents (41.2%) were very satisfied. Cross-tabulation showed that the highest percentage of very satisfied respondents (51.3%) were those who experienced a quick response time. Faster response times improve the quality of patient satisfaction. Patient satisfaction is one of the key indicators of hospital service quality.